Research on heterogeneous distributed fractal image compression algorithm based on parallel genetic algorithm and iterative function - Jian Ning, Han (Journal of physics. Conference series, 2019)
This paper briefly introduces the method and implementation of image compression of heterogeneous distributed genetic and iterative function system (IFS). Based on the traditional parallel genetic algorithm, a heterogeneous distributed model of parallel fractal image compression based on genetic algorithm is implemented, and the corresponding complex model design scheme is put forward. The results show that the algorithm has better search ability, its comprehensive performance such as signal-to-noise ratio/compression time is further improved, the decoding image is similar to the original image, and has high image quality effect.